1999
DOI: 10.1007/s002210050769
|View full text |Cite
|
Sign up to set email alerts
|

Visuomotor adaptation without vision?

Abstract: Anstis (1995) described an aftereffect following treadmill running in which people would inadvertently advance when attempting to run in place on solid ground with their eyes closed. Although originally induced from treadmill running, the running-in-place aftereffect is argued here to result from the absence of sensory information specifying advancement during running. In a series of experiments in which visual information was systematically manipulated, aftereffect strength (AE), measured as the proportional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 22 publications
(24 reference statements)
5
63
1
Order By: Relevance
“…That is, people will overshoot targets in a blind walking task after running on a treadmill with closed eyes for as little as 1 min. This result was previously reported by Durgin, Pelah, and Amiruddin (1998), but they did not include a control condition for which there was no adaptation. Our second experiment, in which we examine the effect of adaptation time on the overshoot effect, suggests that there may be a ceiling on the amount of overshoot that can be obtained using a treadmill.…”
Section: Experimental Strategysupporting
confidence: 83%
See 4 more Smart Citations
“…That is, people will overshoot targets in a blind walking task after running on a treadmill with closed eyes for as little as 1 min. This result was previously reported by Durgin, Pelah, and Amiruddin (1998), but they did not include a control condition for which there was no adaptation. Our second experiment, in which we examine the effect of adaptation time on the overshoot effect, suggests that there may be a ceiling on the amount of overshoot that can be obtained using a treadmill.…”
Section: Experimental Strategysupporting
confidence: 83%
“…The overshoot effect produced in Experiment 1 was quite large (over a meter), and it was similar in size not only to those effects found by Rieser et al (1995) but also to those observed by Durgin et al (1998). Durgin et al (1998) attempted to parametrically compare drift and overshoot aftereffects by varying visual information (eyes open or eyes closed) and treadmill speed.…”
Section: Experiments 2: Overshoot As a Function Of Adaptation Timesupporting
confidence: 55%
See 3 more Smart Citations